2015
DOI: 10.1159/000369160
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Physical Exercise Improved the Cognitive Function of Elderly Males but Did Not Modify Their Blood Homocysteine Levels

Abstract: Background: Physical exercise influences homocysteine (Hcy) concentrations, cognitive function and the metabolic profile. The purpose of this study was to investigate the influence of regular physical exercise on Hcy levels, the metabolic profile and cognitive function in healthy elderly males before and after an endurance exercise program. Methods: Forty-five healthy and sedentary volunteers were randomized into 2 groups: (1) a control group asked not to change their normal everyday activities and not to star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 49 publications
0
14
0
2
Order By: Relevance
“…It seems that the main trigger of this process is the distribution of catecholamines and the reduction of insulin due to aerobic activity and increased lipid oxidation that can reduce the homocysteine level [14] . Studies have shown there is a positive correlation between BMI and low plasma concentrations of folate that can increase the development of hypercholesterolemia [12] . The results of this study are consistent with the cohort study of Park et al which showed there was a positive and significant correlation between BMI and homocysteine [15] .…”
Section: Group Variable Active M(± Sd) Sedentary M(± Sd) P-valuementioning
confidence: 99%
See 2 more Smart Citations
“…It seems that the main trigger of this process is the distribution of catecholamines and the reduction of insulin due to aerobic activity and increased lipid oxidation that can reduce the homocysteine level [14] . Studies have shown there is a positive correlation between BMI and low plasma concentrations of folate that can increase the development of hypercholesterolemia [12] . The results of this study are consistent with the cohort study of Park et al which showed there was a positive and significant correlation between BMI and homocysteine [15] .…”
Section: Group Variable Active M(± Sd) Sedentary M(± Sd) P-valuementioning
confidence: 99%
“…Hence, one of the major issues in the world population is aging and its consequences. Currently, Iran is decline in the quality of life [1] , alterations in inflammatory and coagulation factors, as well as increased levels of homocysteine [12] . Serum homocysteine level is one of the most important predictors of cardiovascular disease with increasing age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Más recientemente, Antunes, Leite, Lee, Barreto, dos Santos, de Sá Souza y de Mello (2016), han puesto de manifiesto que la práctica regular de ejercicio contribuye tanto a la prevención primaria como a la secundaria de distintas enfermedades crónicas, asociándose a un menor riesgo de muerte prematura. Por otro lado, un gran número de expertos en esta temática (Antunes et al, 2015;De Mello, Aquino, Antunes, Bittencourt, Santos-Silva y Tufik, 2013;Warburton, Nicol y Bredin, 2006); sugieren que el deporte influye de manera muy positiva en el sueño y en el estado de ánimo.…”
Section: Introductionunclassified
“…Más recientemente, Antunes, Leite, Lee, Barreto, dos Santos, de Sá Souza y de Mello (2016), han puesto de manifiesto que la práctica regular de ejercicio contribuye tanto a la prevención primaria como a la secundaria de distintas enfermedades crónicas, asociándose a un menor riesgo de muerte prematura. Por otro lado, un gran número de expertos en esta temática (Antunes et al, 2015;De Mello, Aquino, Antunes, Bittencourt, Santos-Silva y Tufik, 2013;Warburton, Nicol y Bredin, 2006); sugieren que el deporte influye de manera muy positiva en el sueño y en el estado de ánimo.De entre todas las modalidades deportivas estudiadas y analizadas, el "running" destaca respecto a las demás, ya que son muchos los corredores que han experimentado el fenómeno conocido como euforia del corredor o high runner; recompensa neurobiológica, que aparece tanto durante, como después de correr largas distancias y que afecta a nivel central (modulador del estado de ánimo, efecto de bienestar) y a nivel periférico, disminuyendo la sensación de dolor (Dietrich y McDaniel, 2004).Cuando una actividad inicialmente beneficiosa para la salud, se transforma en adictiva, pueden llegar a producirse incluso síntomas de abstinencia cuando no se puede realizar ejercicio (Hausenblas y Dowms, 2002). Así, en un estudio reciente (Ruiz-Juan y Zarauz, 2016), se han señalado como posibles causas de la conducta adictiva, la combinación de factores socio-culturales como la búsqueda de una imagen corporal ajustada a los cánones de la sociedad; factores fisiológicos, como el papel que juegan las catecolaminas, la activación del sistema opioide endógeno en el cerebro, la regulación de la interlucina-6, y por supuesto factores psicológicos, en donde la mejora del estado de ánimo, la salud, la autoestima, la confianza y las relaciones sociales que se crean con la práctica deportiva regular, hacen que el deporte pueda llegar a convertirse en un comportamiento adictivo (Kerr, Lindner y Blaydon, 2007).…”
unclassified